SLC39A14 deficiency alters manganese homeostasis and excretion resulting in brain manganese accumulation and motor deficits in mice - Jenkitkasemwong, Supak (Proc Natl Acad Sci U S A, 2018)
Solute carrier family 39, member 14 (SLC39A14) is a transmembrane transporter that can mediate the cellular uptake of zinc, iron, and manganese (Mn). Studies of Slc39a14 knockout (Slc39a14(−/−)) mice have documented that SLC39A14 is required for systemic growth, hepatic zinc uptake during inflammation, and iron loading of the liver in iron overload. The normal physiological roles of SLC39A14, however, remain incompletely characterized. Here, we report that Slc39a14(−/−) mice spontaneously display dramatic alterations in tissue Mn concentrations, suggesting that Mn is a main physiological substrate for SLC39A14. Specifically, Slc39a14(−/−) mice have abnormally low Mn levels in the liver coupled with markedly elevated Mn concentrations in blood and most other organs, especially the brain and bone. Radiotracer studies using (54)Mn reveal that Slc39a14(−/−) mice have impaired Mn uptake by the liver and pancreas and reduced gastrointestinal Mn excretion. In the brain of Slc39a14(−/−) mice, Mn accumulated in the pons and basal ganglia, including the globus pallidus, a region susceptible to Mn-related neurotoxicity. Brain Mn accumulation in Slc39a14(−/−) mice was associated with locomotor impairments, as assessed by various behavioral tests. Although a low-Mn diet started at weaning was able to reverse brain Mn accumulation in Slc39a14(−/−) mice, it did not correct their motor deficits. We conclude that SLC39A14 is essential for efficient Mn uptake by the liver and pancreas, and its deficiency results in impaired Mn excretion and accumulation of the metal in other tissues. The inability of Mn depletion to correct the motor deficits in Slc39a14(−/−) mice suggests that the motor impairments represent lasting effects of early-life Mn exposure.